1965
DOI: 10.1128/aem.13.2.227-231.1965
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leuconostoc mesenteroides in Leavening the Batter of Idli, a Fermented Food of India1

Abstract: , AND K. H. STEINKERAUS. Role of Leuconostoc mesenteroides in leavening of the batter of idli, a fermented food of India. Appl. Microbiol. 13:227-231. 1965.-The fermentation of the batter of idli, a fermented food of India, was studied. The microorganisms responsible for the characteristic changes in the batter were isolated and identified. Although there is a sequential change in the bacterial flora, the predominant microorganism responsible for souring, as well as for gas production, was found to be Leuconos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Studies have shown that Leuc. mesenteroides initiates many fermentation processes such as in tef (Gashe 1985), sauerkraut (Pederson & Albury 1954) and idli (Mukherjee et al 1965). Okafor & Ejiofor (1985) reported the abilities of Leuc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Leuc. mesenteroides initiates many fermentation processes such as in tef (Gashe 1985), sauerkraut (Pederson & Albury 1954) and idli (Mukherjee et al 1965). Okafor & Ejiofor (1985) reported the abilities of Leuc.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk density decreases as the fermentation time increases. This is because 35 PROPERTIES OF IDLI BATTER of the entrapment of air/gas pockets and the function of microorganisms responsible for the different functionality of batter bulk density (Mukherjee et al 1965). DMRT mean values of idli batter bulk density for different blend ratio (2:1, 3:1 and 4:1) (Table 1) at 24 h of fermentation are 0.594, 0.682 and 0.832 (g/cm 3 ), respectively.…”
Section: Bulk Densitymentioning
confidence: 99%
“…It has also been reported that during fermentation, vitamins B and C increase, and also, phytate is about 50% hydrolyzed. According to Mukherjee et al (1965), L. mesenteroides (leavening) and S. faecalis (acid production) develop concomitantly at the soaking stage and continue to multiply following grinding. Marfo et al (1990) reported that the rice and legume batter fermentation reduce phytate content by 45% after 1 day, 75% after 2 days and 80% after 3 days.…”
Section: Introductionmentioning
confidence: 99%
“…The samples taken for microbiological examination were plated with tryptone-glucose-yeast extract agar (Mukherjee et al 1965) and the colonies were counted after incubation at 30°C for 48 h. The moisture in a sample was determined by drying at 115°C for 4 h. The microbial count was expressed on moisture-free basis.…”
Section: Microbial Total Countmentioning
confidence: 99%
“…The changes in the microbial total counts and the physiocochemical properties have been summarized in Table 1. Figure I f demonstrates the predominance of a culture, presumably L. rnesenteroides (Mukherjee et al 1965), when idli batter at 20 h was The plates a, b , c refer to the microflora present in black gram fermentation at 0, 20, and 24 h, respectively. The plates d and e correspond to the microbial population present in rice fermentation at 0 and 20 h , respectively.…”
Section: Bacteriological and Physicochemical Changesmentioning
confidence: 99%